PENGEMBANGAN MEDIA PEMBELAJARAN MENULIS PUISI SEBAGAI UPAYA MENINGKATKAN LITERASI SASTRA DI SEKOLAH DASAR - Nasution, Halimatussakdiah; Siagian, Alberto (Universitas Negeri Medan, 2024)
Abstract: In simpler terms, this describes how various materials, tools, and even technology can be used to enhance the learning process. Think of it as anything that helps students grasp a subject better, be it a physical object like a map or image, a catchy tune, or even an engaging social media platform. Technology plays a big role in this modern twist on learning, with interactive content and online resources like videos fueling student interest and independence. Ultimately, learning media empowers both teachers and students: teachers can offer richer materials and track progress, while students can explore and learn at their own pace. This research used a